Binucleate Rhizoctonia Isolate From Mycorrhizal Pot Cultures: Its Morphological Characteristics And Pathogenicity - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT Kasiamdari, R.S. 2000. Binucleate Rhizoctonia isolate from mycorrhizal pot cultures: its morphological characteristics and pathogenicity.Bio/ogi2(10): 615-628. One isolate of binucleate Rhizoctonia sp. was isolated from cabbage roots grown on the soil of mycorrhizal pot cultures. The isolate was characterized by septate and branched hyphae and simple or branched chains of cells (monilioid cells). Fluorescence of nuclei confirmed that each cell had two nuclei. In vitro experiment was carried out to test the pathogenicity of the isolate to clover, cabbage, tomato and mung bean. The results showed that the isolate caused discoloration and light to dark brown lesions on hypocotyls. The disease severity on the four plant species was significantly different, ranging from 029 to 2.87. In the pot experiment, the isolate was able to infect 40-60% of the roots and was found only in the epidermal cells. The isolate significantly reduced the growth of mung bean and cabbage, but had no effect on the growth of clover and tomato.